Železnodobno naselje Most na Soči = The Iron Age Settlement at Most na Soči Gradbeni izvidi in najdbe = Settlement Structures and Small Finds - Dular, Janez (Opera Instituti Archaeologici Sloveniae, 2016)
Most na Soči ranks among the most prominent prehistoric sites in Europe. It is mainly known for the extensive cemetery from the Early Iron Age, which was first investigated in the late 19th century and revealed over 6000 burials. The rapid growth of the modern village of Most na Soči again led to large-scale archaeological excavations in the 1970s. These were conducted in the span of eleven years and unearthed one of the most significant Iron Age settlements in Slovenia and the wider south-eastern Alpine region.